Microbiolization of cowpea seeds with commercial strains of Trichoderma asperellum and T. harzianum - Ferreira de Lima Cruz, José Manoel; Ricardo de Farias, Otília; Bandeira Medeiros de Moura, Isadora Nayara; Linné, Jéssica Aline; Rodrigues da Silva, Luiz Daniel; Cordeiro do Nascimento, Luciana (Revista Ceres, 2022)
Seed microbiolization has been increasingly contributed to researches due to its beneficial action in the initial growth of seedlings and control of phytopathogens. Thus, the aim of this study was to evaluate the initial growth and control of fungi associated with cowpea seeds by the seed microbiolization with commercial strains of Trichoderma spp. Seeds of cowpea cultivar ‘BRS Gurguéia’ were analyzed in a completely randomized design, with four replications, using five commercial strains based on Trichoderma asperellum and T. harzianum (Trichodermax®, Quality®, Trichodermil®, Agroguard® and Ecotrich®) and two control treatments, represented by untreated seeds (negative control) and the fungicide carbendazim (positive control). Sanity, germination, emergence and electrical conductivity tests of seeds were carried out to confirm the hypotheses. Seed microbiolization with Trichoderma asperellum and Trichoderma harzianum are effective in reducing the incidence of fungi and have antimicrobial activity similar to synthetic fungicide. The strains T. asperellum T-211 (Trichodemax®), T. asperellum URM-5911 (Quality®) e T. harzianum ESALQ-1306 (Trichodermil®) promote increases for seed vigor. The percentage of seed emergence is maximized with the application of strains T. asperellum (Quality® and Trichodemax®). The commercial strains of Trichoderma tested increase the initial growth of cowpea seedlings cv. ‘BRS Gurguéia’.